A Comparison of Self-Assessment of Clinical Skills of OBGYNs Trained in Different Eras [7B]. (May 2016) - Garg, Deepika; Prabakar, Cheruba; Tang, Nancy; Bral, Pedram
Abstract : INTRODUCTION: With the introduction of the bell commission restricting work hours, trainee work hours have diminished. However the degree to which decreased training time has affected graduates' confidence in their abilities has not been assessed. With less hours spent in the hospital without a concurrent increase in residency training time, are newer physicians trained like their older counterparts? Are they just as competent in practicing the breadth of their specialty? METHODS: To investigate the expertise and comfort level of currently practicing OBGYNs in obstetric and gynecologic procedures based on year of graduation from residency. An anonymous questionnaire survey containing 17 questions was administered to 61 practicing OBGYNs at the 2015 ACOG annual national meeting. RESULTS: Twenty four percent of respondents graduated between 1970 and 1990, 56% between 1991 and 2010, and 20% after 2010. All graduates from 1970–1990 were comfortable performing forceps deliveries compared to 45% who graduated after 2010 ( P =.02), with both groups being 100% comfortable with vacuum deliveries. Ninety seven percent of graduates from 1970–1990 felt comfortable tracing the course of the ureter from the pelvic brim to the bladder in comparison to 60% who graduated after 2010 ( P =.02). One hundred percent of graduates from 1970–1990 were comfortable performing a vaginal hysterectomy compared to 75% who graduated after 2010 ( P =.03). CONCLUSION: Older OBGYNs were more comfortable in practicing the full breadth of their specialty compared to their younger counterparts. Future directions include comparing data based on the type and the geographical location of the training program in a larger pool of respondents.